Virtual Laboratory for Practical Learning in Vocational Education Using Nine Events of Instruction Approach - Siregar, Eveline; Kusumawardani, Dwi; Bunyamin, Eskawati Musyarofah (LPPM Undiksha, 2022)
Laboratory is a place where students can recognize and utilize the working system of tools and materials and allow students to gain practical skills through experimentation. However, practicum cannot always be carried out due to limited tools and materials. A virtual laboratory is a media that is made similar and can simulate real laboratory conditions to practice before entering the real laboratory. Therefore the aims of this study is developing virtual laboratory for practical learning in vocational education using nine events of instruction approach. The approach used in this research is the approach of nine instructional events 9 instructional events (9 events in learning) which can be applied in the conventional learning process (face-to-face) and online learning. approach taken in this research is a product-oriented learning development approach and uses a model development. The selection of respondents in this study used a purposive sampling technique. The selected sample is class XII students of vocational high school. Data collection techniques use observations, interviews, questionnaires, and learning outcomes tests. The data that has been collected needs to be analyzed using qualitative analysis and quantitative analysis. This research and development found virtual laboratory for practical learning in vocational education using the nine events of instruction approach which in this approach in learning is a systematic process that has a behavioral approach with a focus on outcomes or behavior during the learning process.